The Relationship Between Social Interaction with The Thematic LEarning Outcomes in Elementary School - Krisna Setiadi (Universitas Sebelas Maret, 2020)
The education sector is one of the sectors affected by the pandemic. Interaction restrictions prohibit schools from conducting face-to-face activities. In the absence of face-to-face learning, the delivery of learning materials is less than optimal. Elementary schools, especially those in grade 2, are severely affected by the absence of face-to-face learning. Grade 2 students who should still need special attention and guidance should be able to study independently at home. Grade 2 students are a transition period from children who are very happy to play to start more seriously in learning science. The limited face-to-face between teachers and students will have an impact on student learning outcomes. Student learning outcomes are good if student interactions both at home, at school, and in the community can run smoothly. Purpose: the purpose of this article is to determine the relationship of children's social interactions to children's learning outcomes. How big is the relationship between the two so that the community can know so that they can determine how to interact well in order to improve their learning outcomes. The results of the study: children's social interaction will greatly affect student learning outcomes at school. With good social interaction will also have good learning outcomes as well.